COMPUTERIZED SYSTEM RENTAL STORES IN PT CIPTA MULYA PERSADA - Yuniarto Prabandoro; Ir. Irfan Ir. Irfan (Jurnal Sistem Informasi, 1999)
Given the system design can be done recording rental, repair data does not need tolook for or correcting one by one, but enough to call a program that became a key orthat we want to fix using the computer as a tool, and for making these reports can alsobe done using printing facility that is the printer equipment.